Redox homeostasis and inflammation in fibroblasts of patients with Friedreich Ataxia: a possible cross talk - Quatrana, Andrea; Petrillo, Sara; Torda, Caterina; De Santis, Eleonora; Bertini, Enrico; Piemonte, Fiorella (Frontiers in Molecular Neuroscience, 2025)
Redox homeostasis is impaired in Friedreich’s Ataxia (FRDA), a neurodegenerative disease caused by the decreased expression of the mitochondrial protein frataxin. Nrf2, the master regulator of tissue redox balance, is defective in the disease, driving cells to ferroptosis. Neuro-inflammation is recently emerging as an additional pathological mechanism in FRDA and has to be understood in order to go deeper into the pathogenesis of the disease. As a functional cross talk between Nrf2 and NF-kB pathways has been previously reported, we wonder if inflammation may be activated in FRDA as a consequence of Nrf2 deficiency. Thus, we analyzed the expression of proteins involved in the antioxidant and inflammatory responses in fibroblasts of patients with FRDA. We found a significant activation of the TLR4/NF-kB/IL-1β axis in patients, associated to a consistent increase of the redox enzymes thioredoxin 1 (TRX1) and glutaredoxin 1 (GLRX1), which are essential to activate NF-kB under oxidative stress conditions. Furthermore, we investigated the role of 4-HNE, a by-product of lipid peroxidation, as a potential mediator between ferroptosis and inflammation in FRDA.